Enhancement of frozen-thawed quality of bull semen after enrichment of docosahexaenoic acid extended in tris- extender - Kaka, Asmatullah; Haron, Wahid; Yimer, Nurhusien; Channo, Abdullah; Raza Jahejo, Ali; Ebrahimi, Mahdi; Hussain Kalhoro, Dildar (ResearchersLinks, 2023)
The present study aimed to depict the quality of frozen-thawed bull sperm extended in Tris-buffered extender (TBE) supplemented with docosahexaenoic acid (DHA). Electro ejaculator was used to collect the semen and ejaculates having ≥ 20 × 109 spermatozoa with an initial motility rate above 70 %, and normal morphology and viability of ≥ 80 % were extended in TBE, to which different concentrations (0, 3, 5, 10 and 15 ng/ml) of DHA were enriched. Semen sample with supplementations were sequentially incubated for 15 minutes at 37 ºC and cooled at 5 ºC for 2 hour than packed in 0.25 ml straws, and cryopreserved in liquid nitrogen for 24 hours. Consequently, straws were thawed at 37C0 for 30 seconds and motility was accessed with the help of computer-assisted semen analyzer (CASA) and membrane integrity with the hypo-osmotic swelling test. Meanwhile morphology, viability and acrosome integrity with contrast-phase microscope (eosin-nigrosin staining) was investigated. Moreover, superoxide dismutase (SOD) assay, a fatty acid composition with gas chromatography and lipid peroxidation TBARS (Thiobarbituric acid reactive substances) content were used for oxidative stress evaluation. Frozen-thawed results showed significant (p < 0.05) enhancement in all sperm parameters with 10 ng/ml of DHA supplementation. DHA improved (p < 0.05) SOD levels in all supplemented groups compared with the control group. Level of TBARS was higher (p < 0.05) at 15 ng/ml as compared to other DHA supplemented and control groups. A dose-dependent increase (P<0.05) was found in C22:6n-3, DHA and n-3PUFA as compared to control group. In conclusion, supplementation of 10 ng/ml of DHA in a Tris-based extender improves the frozen-thawed quality of bull semen.